Determinan Fraud Hexagon Theory dan Indikasi Financial Statement Fraud - Wilantari, Ni Made; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 33 No 1 (2023)DO - 10.24843/EJA.2023.v33.i01.p07, 2023)
This study aims to test the influence of fraud hexagon theory on financial statement fraud. Elements of the causative factors of fraud based on fraud hexagon theory cannot be directly investigated but require proxy variables. Stimulus is projected with financial stability. Opportunity is projected with nature of industry and ineffective monitoring. Rationalization is projected by a change of auditor. Capability is projected with a change of director. Arrogance is projected with a frequent number of CEO's picture. Collution is projected by the ownership of the company by the government or a State-Owned Enterprise or is a private company. The test was conducted on healthcare companies listed on the Indonesia Stock Exchange during the period 2016-2020. Sample selection is done using purposive sampling techniques. Data analysis uses regression panel data. Based on the results of the analysis showed that the variables of financial stability, ineffective monitoring, change in auditor, frequent number of CEO's picture, and state-owned enterprises positively affect financial statement fraud. Nature of industry and change of director have no effect on financial statement fraud. This research provides implications for those who need information about the possibility of financial statement fraud in healthcare companies taking into account influencing factors. Keyword :  Fraud Hexagon Theory; Financial Statement Fraud; Healthcare Company